Changes in Cardiac Tone Regulation with Fatigue after Supra-Maximal Running Exercise - Pierre-Marie Leprêtre; Philippe Lopes; Claire Thomas; Christine Hanon (The Scientific World Journal)
To investigate the effects of fatigue and metabolite accumulation on the postexercicse parasympathetic reactivation, 11 long-sprint runners performed on an outdoor track an exhaustive 400 m long sprint event and a 300 m with the same 400 m pacing strategy. Time constant of heart rate recovery (HRR𝜏), time (RMSSD), and frequency (HF, and LF) varying vagal-related heart rate variability indexes were assessed during the 7 min period immediately following exercise. Biochemical parameters (blood lactate, pH, PO2, PCO2, SaO2, and HCO3−) were measured at 1, 4 and 7 min after exercise. Time to perform 300 m was not significantly different between both running trials. HHR𝜏 measured after the 400 m running exercise was longer compared to 300 m running bouts (183.7±11.6 versus 132.1±9.8 s, 𝑃<0.01). Absolute power density in the LF and HF bands was also lower after 400 m compared to the 300 m trial (𝑃<0.05). No correlation was found between biochemical and cardiac recovery responses except for the PO2 values which were significantly correlated with HF levels measured 4 min after both bouts. Thus, it appears that fatigue rather than metabolic stresses occurring during a supramaximal exercise could explain the delayed postexercise parasympathetic reactivation in longer sprint runs.